Relationships between emoticon usage and recipient groups in students’ text messages - Teh, Phoey Lee *; Ooi, Pei Boon *; Gill, C. M. H. D.* (2020)
Emoticons are pictographic representations of facial expressions that are used to convey emotions in text messages and other similar methods of communication. Most research on emoticons has examined how they are used in public forums rather than in private messaging. Using a sample of undergraduate students (n=106; male 52.83%; mean age 20.26 years, SD 1.93), this study examines the use of emoticons in private text communication. Results reveal that emoticon usage is highest amongst friends, followed by siblings, then parents, other family members and more distant connections. Emoticons representing positive emotions are more commonly used than those representing strong negative emotions. Emoticons representing relief were found to be used particularly within peer group communication, whereas emoticons representing contentment were used more with family members and other, more distant, connections. The use of the “Relieved” emoticon with peers may reflect overcoming the stressors associated with shared educational challenges, whereas using the “Content” emoticon outside peers and family may represent emotional modulation and presentation.